Periodontal diseases in children and adolescent with diabetes mellitus - Yaacob, Munirah; Tin, Myo Han; Ardini, Yunita Dewi; Muhammad Ali, Suhaila; Taib, Mai Nurul Ashikin; Md. Zain, Fuziah; Hua, Janet Hong Yeow (Elsevier, 2019)
The periodontal health status of diabetic children and adolescent was evaluated in this case-control study. 64 subjects were included. Mean age (SD) of the cases and controls were 13.72(2.8) and 13.53(2.5) years. Four periodontal parameters were assessed. HbA1c (%) level within 3 to 6 months prior to check-up was used to defined subjects glycaemic control status. Analysis was done using IBM-SPSS 21. 96.8% of cases have periodontal disease. Probing pocket depth showed significantly deeper mean compared to controls. Higher mean of gingival index were also noticed among the cases. Periodontal screening could be recommended for DM children and adolescent in prevention of severe periodontal disease.